Intradialytic Resistance Training Improves Functional Capacity and Lean Mass Gain in Individuals on Hemodialysis: A Randomized Pilot Trial - Curado Lopes, Lorena Cristina; Mota, Joao Felipe; Prestes, Jonato; Schincaglia, Raquel Machado; Silva, Debora Mendes; Queiroz, Nayara Pedatella; Vaz de Souza Freitas, Ana Tereza; Lira, Fabio Santos [UNESP]; Gondim Peixoto, Maria do Rosario (Elsevier B.V., 2019)
Objective: To compare the effects of high vs moderate loads of intradialytic resistance training (RT) on body composition, sarcopenia prevalence, functional capacity, inflammatory markers, and quality of life (QoL) in individuals on hemodialysis. Design: A pilot randomized clinical trial. Setting: Two hemodialysis centers. Participants: Individuals on hemodialysis (N=80; 51% men, aged 30-75y) in treatment for at least 3 months, adequately dialyzed (Kt/V >= 1.2, where K is dialyzer clearance in mL/min, t is time, and V is volume of water) with vascular access via arteriovenous fistula. Interventions: The 12 weeks of intradialytic RT was performed 3 times per week. The training groups were: high-load intradialytic group (HLG, 8-10 repetitions), moderate-load intradialytic group (MLG, 16-18 repetitions), and control group (CG, stretching exercise). The total training volume was equalized among training groups. Main Outcome Measures: Lean leg mass was assessed by a dual-energy x-ray absorptiometry; functional capacity was assessed by Short Physical Performance Battery and Timed Up and Go test; and QoL was assessed by Kidney Disease QoL Instrument, inflammatory markers, and sarcopenia. Results: After the training period, the HLG increased lean leg mass compared with the CG. The HLG also displayed improvements in the pain and physical function domains. The skeletal muscle index and functional capacity increased in both RT protocols. The prevalence of sarcopenia was reduced 14.3% and 25% in the MLG and HLG, respectively, while there was an increase of 10% in the CG. No differences were observed in cytokines after intervention. Conclusions: High-load intradialytic RT was associated with gains in lean leg mass and QoL while functional capacity, appendicular muscle mass, and sarcopenia status were improved regardless of the RT load. (C) 2019 by the American Congress of Rehabilitation Medicine
Keywords: Quality of life; Rehabilitation; Renal dialysis; Resistance training; Sarcopenia